Pristine Hollow Metal–Organic Frameworks: Design, Synthesis and Application - Qiu, Tianjie; Gao, Song; Liang, Zibin; Wang, De‐Gao; Tabassum, Hassina; Zhong, Ruiqin; Zou, Ruqiang (Angewandte Chemie International Edition, 2021)
Metal–organic frameworks (MOFs), featuring porous crystalline structures with coordinated metal nodes and organic linkers, have recently found increasing interest in diverse applications. By virtue of their versatile and highly tunable compositions and structures, constructing hollow architectures will further endow MOFs with enhanced properties and designability, exceeding the molecular scale. MOFs could be considered as promising building units to fabricate complex hollow nanocomposites with faster mass transport, multiple active components, more exposed active sites, and better compatibility than bulk MOFs. To construct a promising blueprint for hollow pristine MOFs, this review provides a comprehensive overview for structural design strategies and applications of hollow pristine MOFs. We will highlight the merits, challenges and future potential by structuring and applying MOFs in sensing, separation, storage, catalysis, environmental remediation, photochemical and electrochemical energy conversion. This review might pave a new avenue for future development of novel pristine hollow MOFs. Hollow MOFs show outstanding properties in catalysis, separation, storage, sensing and energy applications resulting from their tunable composition/structure versatility and designability, exceeding the molecular scale. In this review, synthetic strategies for engineering hollow MOFs and their applications are systematically summarized.